2023
DOI: 10.2355/isijinternational.isijint-2022-306
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Humic Substances in Pelletizing Binders: Preparation, Interaction Mechanism, and Process Characteristics

Abstract: Humic acid is inexpensive, and has a wide range of sources and a strong adsorption force with the surface of iron ore, and the size of its adsorption force is affected by some factors such as humic acid concentration, pH of the solution, and metal cations. The modified humic acid pellet binder (MHA) with strong adhesion and high viscosity was obtained through the separation and purification of solid wastes such as lignite and weathered coal and chemical modification treatment and successfully applied in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…HA is a macromolecular compound [32,33], and the chemical properties are different depending on the source and extraction method. In common, an HA molecule carries multiple carboxy and phenolic hydroxy groups, although its structure varies with the geographical origin, age, climate, and biological conditions [6,[34][35][36]. Here, since the number of carboxy groups is higher than that of phenolic hydroxy groups in an HA molecule and carboxy groups are more acidic than phenolic hydroxy groups, the pK a value ranges from 4-6.…”
Section: Effect Of Phmentioning
confidence: 99%
“…HA is a macromolecular compound [32,33], and the chemical properties are different depending on the source and extraction method. In common, an HA molecule carries multiple carboxy and phenolic hydroxy groups, although its structure varies with the geographical origin, age, climate, and biological conditions [6,[34][35][36]. Here, since the number of carboxy groups is higher than that of phenolic hydroxy groups in an HA molecule and carboxy groups are more acidic than phenolic hydroxy groups, the pK a value ranges from 4-6.…”
Section: Effect Of Phmentioning
confidence: 99%
“…HA and FA molecules rely on a large number of active functional groups to generate adsorption forces such as ligand exchange and electrostatic interaction with Fe 2+ /Fe 3+ on the surface of mineral particles [69], while with the increase in HA content, colloid action is enhanced, which adheres to and wraps around mineral particles, resulting in enhanced bridging between mineral particles and tight agglomeration, thus substantially increasing HA and FA molecules rely on a large number of active functional groups to generate adsorption forces such as ligand exchange and electrostatic interaction with Fe 2+ /Fe 3+ on the surface of mineral particles [69], while with the increase in HA content, colloid action is enhanced, which adheres to and wraps around mineral particles, resulting in enhanced bridging between mineral particles and tight agglomeration, thus substantially increasing the green pellet strength [70,71]. Numerous studies have shown [72,73] that the adsorption concentration of HA on magnetite/hematite increases with increasing HA concentration and decreases with increasing pH [74], while metal cations change the stretching and curling of FA molecules, leading to the cohesion of FA together, thus increasing the viscosity of FA solution and promoting bridging between FA and magnetite surfaces, allowing more FA to be adsorbed on the mineral surface [75]. Therefore, the viscosity and adsorption density of humic acid-based pellet binder can be increased by adjusting the pH and concentration of the HA/FA solution or adding metal cations to obtain better green pellet strength [76].…”
Section: The Application Effect Of Starch In the Pelletsmentioning
confidence: 99%
“…Qiu et al [ 16 ] utilized organic binders to prepare pelletized ore and found that, compared to pellets prepared using bentonite, the resulting pellets had a higher iron grade and lower impurity content [ 17 ]. Humic acid, as an organic binder and a biomass-derived substance, exhibits strong adsorption capacity on the surface of iron ore, thereby enhancing the strength of green pellets [ 18 , 19 ]. Currently, there is limited research on the preparation of limonite pellets using humic acid as a binder, necessitating further investigation into humic acid-based limonite pellets.…”
Section: Introductionmentioning
confidence: 99%